The impact of one unit on Sindh’s political future after its abolition - Taha Shabbir; Abdul Shakoor Chandio; Syed Shuja Uddin; Asim Ali (International Journal of Humanities and Innovation (IJHI), 2021)
Pakistan's federalism problem dates all the way back to the establishment of the republic. Pakistan was established during many problems, many of which involved the state's government and administration. After Pakistan's inception, Federalism has been recognized as a political structure. The Muslim League was Pakistan's democratic body, and it called for the provinces of United India to have complete provincial autonomy. In the other side, the Congress favored a moderate federation. Due to the Muslim League's extensive past and tradition, it has been forced to recognize Federalism as a state system. Karachi, a major commercial center in Sindh, was annexed by the federal government and incorporated into its region. As a consequence of this undemocratic act, Sindh's ministry was dissolved, and Karachi was put under federal administration. The smaller provinces were compelled to form One Unit as a result of this development. The One-unit structure scrapped Sindh's territorial position and fundamentally altered its demography. After Bengal's dismemberment, Punjab became the only ruling state, controlling the state structure. Sindh remained marginalized in this province. Sindh has always met with the same fate. Furthermore, Pakistan's constitutions made no provision for Sindh's provincial hegemony. This thesis makes an empirical attempt to examine the historical connection between the Centre and Sindh.